Mild hypothermia induces incomplete left ventricular relaxation despite spontaneous bradycardia in pigs. (9th January 2015) - Schwarzl, M.; Alogna, A.; Zirngast, B.; Steendijk, P.; Verderber, J.; Zweiker, D.; Huber, S.; Maechler, H.; Pieske, B. M.; Post, H.
Abstract Aim Mild hypothermia (MH) decreases left ventricular (LV) end‐diastolic capacitance. We sought to clarify whether this results from incomplete relaxation. Methods Ten anaesthetized pigs were cooled from normothermia (NT, 38 °C) to MH (33 °C). LV end‐diastolic pressure (LVPed), volume (LVVed) and pressure–volume relationships (EDPVRs) were determined during stepwise right atrial pacing. LV capacitance (i.e. LVVed at LVPed of 10 mmHg, LV VPed10) was derived from the EDPVR. Pacing‐induced changes of diastolic indices (LVPed, LVVed and LV VPed10) were analysed as a function of (i) heart rate and (ii) the ratio between diastolic time interval (t‐dia) and LV isovolumic relaxation constant τ, which was calculated using a logistic fit (τL) and monoexponential fit with zero asymptote (τZ) and nonzero asymptote (τNZ). Results Mild hypothermia decreased heart rate (85 ± 4 to 68 ± 3 bpm), increased τL (22 ± 1 to 57 ± 4 ms), τZ (26 ± 2 to 56 ± 5 ms) and τNZ (41 ± 1 to 96 ± 5 ms), decreased t‐dia/τ ratios, and shifted the EDPVR leftwards compared to NT (all P < 0.05). During NT, pacing at ≥140 bpm shifted the EDPVR progressively leftwards. During MH, relationships between diastolic indices and heart rate were shifted towards lower heart rates compared to NT. However, relationships between diastolic indices and t‐dia/τ during NT and MH were superimposable. Conclusion We conclude that the loss of LV end‐diastolic capacitance during MH can be explained at least in part by slowed LV relaxation. MH thereby is an example of incomplete LV relaxation at a spontaneous low heart rate. Caution may be advised, when heart rate is increased in patients treated with MH.